Farzana : the woman who saved an empire - Keay, Julia (I.B. Tauris, 2014)
Amongst the riches of 19th century India, as the British fought their way across Mughal territory, an orphaned street-girl is brought to court to perform for the Emperor. That girl was Farzana, and she would become a courtesan, a leader of armies, a treasured defender of the last Mughal emperor and the head of one of the most legendary courts in history. In this beautifully written book, the author's last, Julia Keay weaves a story which spans the Indian continent and the end of a golden era in Indian history, the story of a nobody who became a teenage seductress and died one of the richest an.